2007
DOI: 10.1063/1.2806194
|View full text |Cite
|
Sign up to set email alerts
|

Electrical characteristics of palladium Schottky contacts to hydrogen peroxide treated hydrothermally grown ZnO

Abstract: The formation of Schottky barrier contacts to hydrogen peroxide treated ZnO has been investigated. Low resistivity hydrothermally grown single crystal ZnO wafers of n-type were used. Pd contacts deposited on organic solvent cleaned O face (0001¯) showed Ohmic behavior, while on the H2O2 treated O face up to nine orders of magnitude in rectification of the current was obtained for biases of −2 and +2V. Concurrently, the surface roughness increases from 1.0±0.5 up to 2.0±0.5nm due to the H2O2 treatment. A majori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 66 publications
(76 reference statements)
0
44
0
Order By: Relevance
“…This treatment is commonly used for the preparation of Schottky diodes on ZnO and has proven to lead to highly rectifying diodes. 49 Between 10 and 15 Pd contacts with a thickness in the range of $150-200 nm were deposited onto the samples via electron beam evaporation, using a Si shadow mask with pad areas of 0.7 Â 10 À3 to 4.2 Â 10 À3 cm 2 . Eutectic InGa was used as Ohmic back contact.…”
Section: Methodsmentioning
confidence: 99%
“…This treatment is commonly used for the preparation of Schottky diodes on ZnO and has proven to lead to highly rectifying diodes. 49 Between 10 and 15 Pd contacts with a thickness in the range of $150-200 nm were deposited onto the samples via electron beam evaporation, using a Si shadow mask with pad areas of 0.7 Â 10 À3 to 4.2 Â 10 À3 cm 2 . Eutectic InGa was used as Ohmic back contact.…”
Section: Methodsmentioning
confidence: 99%
“…For example, surface conductivity may affect the properties of gas sensors, 4 and also devices that incorporate Schottky barriers. 5 Recently, we have shown that nearly all commercially available ZnO wafers ͑that we have examined͒ have a conductive surface layer ͑CSL͒ that totally dominates the sample conductance at low temperatures and sometimes strongly influences the conductance even at room temperature. 6 Thus, to accurately characterize the total electrical properties of a wafer, it is necessary to separate the bulk and surface contributions.…”
mentioning
confidence: 99%
“…1 Metal/ZnO interfaces are essential to all ZnO electronic device applications, yet fabricating high quality and thermally stable rectifying and Ohmic ZnO contacts remains a challenge and their electronic properties have only recently been explored in detail. [2][3][4][5][6][7] Metals on semiconductors seldom obey the Schottky-Mott theory, i.e., their Schottky barrier heights are not proportional to their work functions. 8 Previous ZnO surface studies revealed the importance of surface adsorbates, near-interface native defects, and thermally induced interface chemical interactions at metal/ZnO contacts.…”
mentioning
confidence: 99%